Lithium manganese iron phosphate positive electrode material and preparation method thereof, positive plate and battery

By adopting a multi-layered coated structure of lithium manganese iron phosphate positive electrode material, high ferromanganese iron phosphate I and low ferromanganese iron phosphate II, combined with carbon material and the second cladding layer of inorganic solid electrolyte, the dissolution and polarization problems when the manganese content is high are solved, and high energy density and excellent cycling performance are achieved.

CN119673991APending Publication Date: 2025-03-21JINLONGYU NEW ENERGY (SHENZHEN) CO LTD

Patent Information

Application Number
CN202411788442.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing lithium manganese iron phosphate positive electrode material is easily dissolved when the manganese content is high, resulting in increased polarization of the battery, deterioration of the cycleability, and it is difficult to effectively improve the energy density and circulation performance of the battery.

Method used

The lithium manganese iron phosphate positive electrode material adopts a multi-layer clad structure, the core is lithium manganese iron phosphate I, the first clad layer is lithium manganese iron phosphate II, and the second clad layer contains carbon material and inorganic solid electrolyte. By regulating the mass ratio of manganese elements to iron, the influence of the Jahn-Teller effect is reduced, and the circulation performance and energy density of the material are improved.

Benefits of technology

The cycling performance and energy density of lithium manganese iron phosphate cathode material is significantly improved, the irreversible changes in the material structure are reduced, the electrochemical performance is enhanced, and the structure of the material is stabilized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119673991A_ABST
    Figure CN119673991A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium manganese iron phosphate positive electrode material and a preparation method thereof, a positive plate and a battery, and belongs to the technical field of methods or devices for directly converting chemical energy into electric energy. The lithium manganese iron phosphate positive electrode material comprises an inner core, a first coating layer arranged on the surface of the inner core and a second coating layer arranged on the surface of the first coating layer, the inner core is lithium manganese iron phosphate I, the first coating layer comprises lithium manganese iron phosphate II, and the second coating layer comprises a carbon material and an inorganic solid electrolyte. The lithium manganese iron phosphate positive electrode material not only can endow a battery with relatively high energy density, but also can endow the battery with excellent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to a lithium manganese iron phosphate positive electrode material and a preparation method thereof, a positive electrode sheet, and a battery. Background Art

[0002] Lithium iron manganese phosphate is a solid solution of lithium iron phosphate and lithium manganese phosphate. It maintains the stable olivine structure of lithium iron phosphate and introduces the manganese element of the high voltage platform to increase the charging voltage from 3.4V of lithium iron phosphate to 4.1V. At the same time, it can be seen from the mass energy density (Wh / kg) = battery gram capacity (mAh / g) × operating voltage that under similar gram capacity conditions, the higher the voltage, the greater the mass energy density. The high voltage characteristics of manganese make lithium iron manganese phosphate have a higher voltage platform, which in turn increases the energy density of the battery by 15% to 20% in theory, thereby significantly improving the battery's endurance. Moreover, the safety performance of lithium iron manganese phosphate is better than that of ternary positive electrode materials, and the theoretical cycle life is longer. It has a low dependence on rare metals and can be produced on the same line with lithium iron phosphate at a lower cost.

[0003] However, when the manganese content is low, the voltage platform of lithium manganese iron phosphate is limited, and it is difficult to effectively improve the energy density of the battery; when the manganese content is high, the manganese element is easily dissolved due to the Jahn-Teller effect during the charge and discharge process of lithium manganese iron phosphate, the battery polarization increases, and the manganese element dissolved in the electrolyte will also be deposited on the surface of the negative electrode, destroying the SEI layer structure, causing capacity loss, thereby making the battery cycle worse; that is, the higher the manganese content, the greater the battery energy density, but the battery capacity will decrease and the cycle life will decay. At present, the comprehensive performance of lithium manganese iron phosphate with a manganese iron ratio of 6 / 4 is good, and it is the mainstream lithium manganese iron phosphate positive electrode material on the market, but its improvement in battery energy density and cycle performance needs to be improved. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a lithium iron manganese phosphate positive electrode material and a preparation method thereof, a positive electrode sheet, and a battery.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] In a first aspect, the present invention provides a lithium iron manganese phosphate positive electrode material, the lithium iron manganese phosphate positive electrode material comprising a core, a first coating layer disposed on the surface of the core, and a second coating layer disposed on the surface of the first coating layer;

[0007] The core is lithium iron manganese phosphate I, the first coating layer includes lithium iron manganese phosphate II, and the second coating layer includes carbon material and inorganic solid electrolyte;

[0008] The molar ratio of manganese element to iron element in the lithium manganese iron phosphate I is (0.75-0.9):(0.07-0.24);

[0009] The molar ratio of manganese element to iron element in the lithium manganese iron phosphate II is (0.35-0.5):(0.47-0.64);

[0010] Taking the total mass of the core and the first coating layer as 100%, the mass of the core accounts for 70% to 90%;

[0011] The mass ratio of the total mass of the core and the first coating layer to the mass of the inorganic solid electrolyte is (85-94):(6-15); the mass content of the carbon material in the lithium manganese iron phosphate positive electrode material is 1.5%-2%.

[0012] The present invention uses lithium iron manganese phosphate seed crystals as the core, forms a first coating layer on the surface of the core, and forms a second coating layer on the surface of the first coating layer, and utilizes lithium iron manganese phosphate I with a high manganese-iron ratio to promote the uniform nucleation and growth of lithium iron manganese phosphate II with a low manganese-iron ratio to form the first coating layer. The first coating layer wrapped on the surface of the core can not only effectively prevent the electrolyte from contacting the core, but also reduce the negative impact of the Jahn-Teller effect, so that after being combined with the second coating layer containing carbon material and inorganic solid electrolyte, the lithium iron manganese phosphate positive electrode material is given excellent cycle performance and higher energy density.

[0013] In addition, by regulating the mass ratio of manganese to iron in lithium iron phosphate I and lithium iron phosphate II, not only can the voltage be increased to improve the energy density, but also the influence of the Jahn-Teller effect can be significantly weakened to reduce the irreversible changes in the material structure, thereby improving the rate performance of the lithium iron phosphate positive electrode material; the carbon material and inorganic solid electrolyte in the second coating layer can not only improve the conductivity of the lithium iron phosphate positive electrode material, and construct an effective lithium ion diffusion channel, thereby improving its electrochemical performance; at the same time, it can also stabilize the structure of the lithium iron phosphate positive electrode material, reduce and inhibit the side reactions caused by contact with the electrolyte.

[0014] Optionally, in terms of molar fractions, the manganese element in the lithium manganese iron phosphate I can be 0.75 parts, 0.8 parts, 0.85 parts, or 0.9 parts, and the iron element can be 0.07 parts, 0.15 parts, 0.2 parts, or 0.24 parts; the manganese element in the lithium manganese iron phosphate II can be 0.35 parts, 0.4 parts, 0.45 parts, or 0.5 parts, and the iron element can be 0.47 parts, 0.5 parts, 0.55 parts, 0.6 parts, or 0.64 parts.

[0015] Optionally, taking the total mass of the core and the first coating layer as 100%, the mass proportion of the core can be any one of 70%, 73%, 75%, 78%, 80%, 82%, 85%, 88%, 90% or any two of the range values.

[0016] Optionally, in terms of weight percentage, the total mass of the inner core and the first coating layer can be 85 parts, 86 parts, 87 parts, 88 parts, 89 parts, 90 parts, 91 parts, 92 parts, 93 parts, or 94 parts, and the weight percentage of the inorganic solid electrolyte can be 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, or 15 parts.

[0017] Optionally, the mass content of the carbon material in the lithium manganese iron phosphate positive electrode material can be any one of 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, or any two of the range values.

[0018] As a preferred embodiment of the lithium iron manganese phosphate positive electrode material of the present invention, the lithium iron manganese phosphate positive electrode material satisfies at least one of the following conditions:

[0019] a. The molar ratio of manganese to iron in the lithium manganese iron phosphate positive electrode material is (0.63-0.85):(0.1-0.33); optionally, in terms of molar fractions, the manganese element in the lithium manganese iron phosphate positive electrode material can be 0.63, 0.65, 0.68, 0.71, 0.72, 0.73, 0.79, 0.83, or 0.85, and the molar fraction of iron can be 0.1, 0.14, 0.19, 0.23, 0.24, 0.25, 0.26, 0.31, or 0.33.

[0020] b. The particle size D of the core 50 0.6 to 1.2 μm; Optionally, the particle size D of the core 50 Specifically, the value may be within any one range of 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, and 1.2 μm, or any two of the ranges.

[0021] c. The inorganic solid electrolyte includes LATP (lithium aluminum titanium phosphate), LAGP (lithium aluminum germanium phosphate), LLTO (lithium lanthanum titanate), LLZO (Li7La3Zr2O 12 ) at least one of the following; the chemical formula of the lithium aluminum titanium phosphate is Li 1+a Al a Ti 2-a (PO4)3, wherein 0≤a≤0.5; the chemical formula of the lithium germanium aluminum phosphate is Li 1+b Al bGe 2-b (PO4)3, where 0 ≤ b ≤ 0.5; the chemical formula of the lithium lanthanum titanate is Li 3c La 2 / 3-c Ti d T 1-d O3, where 0 < c < 2 / 3, 0 < d ≤ 1, and T is at least one of Nb, W, Ti, Hf, Ru, Mo, Nd, Ba, Ga, In, Ge, Sn, Sb, Se.

[0022] As a preferred embodiment of the lithium iron manganese phosphate cathode material of the present invention, the lithium iron manganese phosphate I and / or the lithium iron manganese phosphate II include doping elements.

[0023] As a preferred embodiment of the lithium iron manganese phosphate cathode material of the present invention, based on the total molar amount of manganese element, iron element and doping element being 100%, at least one of the following is satisfied:

[0024] a. The molar content of the doping element in the lithium iron manganese phosphate I is 1% - 3%; optionally, the molar content of the doping element in the lithium iron manganese phosphate I can specifically be any one or the range value of any two of 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%.

[0025] b. The molar content of the doping element in the lithium iron manganese phosphate II is 1% - 3%; the molar content of the doping element in the lithium iron manganese phosphate II can specifically be any one or the range value of any two of 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%.

[0026] In the second aspect, the present invention provides a preparation method of the above lithium iron manganese phosphate cathode material, including the following steps:

[0027] S1. Mix a lithium source, an iron source, a manganese source, a phosphorus source, a doping metal source, a carbon source and a solvent, grind them to obtain a mixed slurry I, spray-dry it, and then conduct a first sintering in an inert gas atmosphere, and crush it to obtain lithium iron manganese phosphate seeds;

[0028] S2. Mix the lithium iron manganese phosphate seeds in S1 with a lithium source, an iron source, a manganese source, a phosphorus source, a doping metal source, a carbon source and a solvent, grind them to obtain a mixed slurry II, spray-dry it, and then conduct a second sintering in an inert gas atmosphere, and crush it to obtain a lithium iron manganese phosphate precursor material;

[0029] S3, mixing the lithium iron manganese phosphate precursor material in S2 with an inorganic solid electrolyte, a carbon source and a solvent, sand-milling to obtain a mixed slurry III, spray-drying the mixed slurry, sintering the mixed slurry for the third time in an inert gas atmosphere, and crushing the mixed slurry to obtain a lithium iron manganese phosphate positive electrode material;

[0030] The temperature of the first sintering is ≤650°C and the time is ≤8h; the temperature of the second sintering is ≤750°C and the time is ≤15h; the temperature of the third sintering is ≤600°C and the time is ≤8h.

[0031] It should also be noted that the carbon source added in step S1 is only used to reduce the non-positive divalent iron and manganese elements in the iron source and manganese source, and reduce them to a positive divalent state to facilitate the formation of pure-phase lithium manganese iron phosphate seed crystals; if the valence state of the manganese iron element in the iron source or manganese source is already a positive divalent state, there is no need to add a carbon source.

[0032] Preparation of 1 mol LiMn using Li2CO3, NH4H2PO4, FePO4 and MnO2 0.7 Fe 0.28 Mg 0.02 PO4, the carbon source is selected as glucose, and the amount of glucose added is calculated as follows:

[0033] Preparation of 1 mol LiMn 0.7 Fe 0.28 Mg 0.02 PO4 requires 0.7 mol of MnO2 and 0.28 mol of FePO4. The manganese element in MnO2 is tetravalent, and the iron element in FePO4 is trivalent. The following chemical equation shows that:

[0034] 4Fe 3+ +C→4Fe 2+ +C 4+ , 2Mn 4+ +C→2Mn 2+ +C 4+ ;

[0035] The carbon required to reduce iron is: 1 / (4 / 0.28)×12≈0.84g;

[0036] The carbon required to reduce manganese is: 1 / (2 / 0.7)×12≈4.20g;

[0037] The total carbon used to reduce the manganese iron element is 4.2+0.84=5.04g. At the same time, since the carbon content of glucose is 40%, the amount of glucose that needs to be added is 5.04÷0.4=12.6g.

[0038] Similarly, the carbon source added in step S2 is only used to reduce the non-positive divalent iron and manganese elements in the iron source and manganese source, and reduce them to a positive divalent state to facilitate the generation of pure-phase lithium manganese iron phosphate material; if the valence state of the manganese iron element in the iron source or manganese source is already a positive divalent state, there is no need to add a carbon source.

[0039] In addition, the role of the carbon source added in step S3 is to mix with the inorganic solid electrolyte to perform surface coating modification on the lithium manganese iron phosphate, thereby improving the conductivity of the lithium manganese iron phosphate.

[0040] As a preferred embodiment of the method for preparing the lithium manganese iron phosphate positive electrode material of the present invention, at least one of the following conditions is met:

[0041] a. The temperature of the first sintering is 350-650°C, and the time is 3-8h. Optionally, the temperature of the first sintering can be any one of 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, or any two of the range values, and the time can be any one of 3h, 4h, 5h, 6h, 7h, 8h, or any two of the range values.

[0042] b. The temperature of the second sintering is 550-750°C, and the time is 4-15h. Optionally, the temperature of the second sintering can be any one of 550°C, 600°C, 650°C, 700°C, 750°C, or any two of the range values, and the time can be any one of 4h, 6h, 8h, 10h, 13h, 15h, or any two of the range values.

[0043] c. The temperature of the third sintering is 500-600°C, and the time is 2-6h. Optionally, the temperature of the third sintering can be any one of 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, or any two of the range values, and the time can be any one of 2h, 3h, 4h, 5h, 6h, or any two of the range values.

[0044] As a preferred embodiment of the method for preparing the lithium manganese iron phosphate positive electrode material of the present invention, at least one of the following conditions is met:

[0045] a. The particle size D after sand grinding described in S1 50 150-300 nm, specifically 160 nm, 200 nm, 240 nm, 280 nm; the particle size D after crushing 50 0.6-1.2 μm, specifically 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm;

[0046] b. The particle size D after sand grinding described in S2 50200-380 nm, specifically 250 nm, 300 nm, 350 nm; the particle size D after crushing 50 1.5 to 2.1 μm, specifically 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm;

[0047] c. The particle size D after sand grinding described in S3 50 50 to 120 nm, specifically 70 nm, 90 nm, 110 nm; the particle size D after crushing 50 It is 2.3 to 3.0 μm, specifically 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, and 2.9 μm.

[0048] The particle size D of the above-mentioned sand-milled particles is 50 And the particle size D of the crushed particles 50 All can be measured using Mastersizer 3000 laser particle size analyzer.

[0049] As a preferred embodiment of the method for preparing the lithium manganese iron phosphate positive electrode material of the present invention, at least one of the following conditions is met:

[0050] a. The molar ratio of Li in the lithium source, Fe in the iron source, Mn in the manganese source, P in the phosphorus source and the doping element in the doping metal source in S1 is (1-1.06):(0.07-0.24):(0.75-0.9):(1-1.05):(0.01-0.03);

[0051] b. The molar ratio of Li in the lithium source, Fe in the iron source, Mn in the manganese source, P in the phosphorus source and the doping element in the doping metal source in S2 is (1-1.06):(0.47-0.64):(0.35-0.5):(1-1.05):(0.01-0.03);

[0052] c. The doping element sources described in S1 and S2 both include a magnesium source, which is at least one of magnesium oxide, magnesium hydrogen phosphate, magnesium hydroxide, and magnesium carbonate;

[0053] d. The carbon sources described in S1, S2 and S3 are independently selected from at least one of glucose, sucrose, polypropylene, acetylene black and polyvinylpyrrolidone-K30;

[0054] e. The lithium sources described in S1 and S2 are independently selected from at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium nitrate, lithium oxalate, lithium acetate and lithium phosphate;

[0055] f. The iron sources described in S1 and S2 are independently selected from at least one of ferric oxalate, ferric phosphate, ferric oxide, ferric hydroxide and ferric acetate;

[0056] The manganese sources described in g, S1 and S2 are independently selected from at least one of manganese carbonate, manganese oxalate, manganese dioxide, manganese trioxide and manganese tetraoxide;

[0057] The phosphorus sources described in h, S1 and S2 are independently selected from at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid and lithium dihydrogen phosphate.

[0058] In a third aspect, the present invention provides a positive electrode sheet, comprising a current collector and a coating provided on at least one side of the current collector, wherein the coating comprises the above-mentioned lithium manganese iron phosphate positive electrode material.

[0059] In a fourth aspect, the present invention provides a battery, comprising the above-mentioned positive electrode sheet.

[0060] Compared with the prior art, the present invention has the following beneficial effects:

[0061] The present invention uses lithium iron manganese phosphate seed crystals as the core, forms a first coating layer on the surface of the core, and forms a second coating layer on the surface of the first coating layer, and utilizes lithium iron manganese phosphate I with a high manganese-iron ratio to promote the uniform nucleation and growth of lithium iron manganese phosphate II with a low manganese-iron ratio to form the first coating layer with a low manganese-iron ratio. The first coating layer wrapped on the surface of the core can not only effectively prevent the electrolyte from contacting the core, but also reduce the negative impact of the Jahn-Teller effect, so that after being combined with the second coating layer containing a carbon material and an inorganic solid electrolyte, the lithium iron manganese phosphate positive electrode material is given excellent cycle performance and higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is a SEM image of the lithium manganese iron phosphate positive electrode material in Example 1;

[0063] Figure 2 This is a graph of the gram capacity of the button cell corresponding to the lithium manganese iron phosphate positive electrode material in Example 1. DETAILED DESCRIPTION

[0064] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0065] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.

[0066] Example 1

[0067] This embodiment provides a lithium manganese iron phosphate positive electrode material, and the preparation method thereof comprises the following steps:

[0068] S1, 4 mol of Li2CO3 (lithium source), 1.36 mol of FePO4 (iron source), 6.4 mol of MnCO3 (manganese source), 6.64 mol of NH4H2PO4 (phosphorus source), 0.24 mol of MgO (doping element source), 10.2 g of glucose (carbon source) and 3000 g of water were added to a sand mill containing 2 kg of zirconium beads (diameter of zirconium beads is 0.3-0.4 mm) and mixed and ground to obtain a first mixed slurry (particle size D 50 =200nm); then the first mixed slurry was spray dried (the inlet air temperature of the sprayer was set to 220±5℃, and the outlet air temperature was set to 100±5℃), and then the first sintering was carried out under nitrogen atmosphere protection (sintering at 500℃ for 5h), and after cooling, it was crushed by air flow mill to obtain pure phase lithium manganese iron phosphate seed crystals (particle size D 50 =0.8 μm);

[0069] S2, 1 mol of Li2CO3 (lithium source), 1.16 mol of FePO4 (iron source), 0.8 mol of MnCO3 (manganese source), 0.84 mol of NH4H2PO4 (phosphorus source), 0.04 mol of MgO (doping element source), 8.7 g of glucose (carbon source) and 800 g of water were added to a sand mill containing 2 kg of zirconium beads (diameter of the zirconium beads was 0.4-0.6 mm) and mixed and ground to obtain a second slurry (particle size D 50 =300nm); then the second slurry was evenly mixed with the pure phase lithium manganese iron phosphate seed crystals in S1 and spray-dried (the inlet air temperature of the sprayer was set to 220±5°C, and the outlet air temperature was set to 100±5°C), and then sintered for the second time under nitrogen atmosphere protection (sintered at 650°C for 10h), and after cooling, it was crushed by air flow mill to obtain lithium manganese iron phosphate precursor (particle size D 50 =1.8 μm);

[0070] S3, 174.7g of LATP (inorganic solid electrolyte Li 1.2 Al 0.2 Ti 1.8 (PO4) 3), 89 g of glucose (carbon source) and 1800 g of water were added to a sand mill containing 2 kg of zirconium beads (diameter of the zirconium beads was 0.2-0.4 mm) and mixed and ground to obtain a third slurry (particle size D 50=80nm); then the third slurry was mixed evenly with the lithium iron manganese phosphate precursor in S2 (the mass ratio of the lithium iron manganese phosphate precursor to LATP was 90:10) and then spray dried (the inlet air temperature of the sprayer was set to 220±5°C, and the outlet air temperature was set to 100±5°C), and then sintered for the third time under nitrogen atmosphere protection (sintered at 550°C for 4h), and after cooling, it was crushed by air flow mill to obtain lithium iron manganese phosphate positive electrode material (particle size D 50 =2.7μm, such as Figure 1 shown).

[0071] Example 2

[0072] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0073] In step S1, Li2CO3 is 3.5 mol, FePO4 is 1.54 mol, MnCO3 is 5.25 mol, NH4H2PO4 is 5.46 mol, MgO is 0.21 mol, glucose is 11.6 g, and water is 2600 g;

[0074] In step S2, Li2CO3 is 1.5 mol, FePO4 is 1.89 mol, MnCO3 is 1.05 mol, NH4H2PO4 is 1.11 mol, MgO is 0.06 mol, glucose is 14.2 g, and water is 1100 g.

[0075] Example 3

[0076] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0077] In step S1, Li2CO3 is 4.5 mol, FePO4 is 1.98 mol, MnCO3 is 6.75 mol, NH4H2PO4 is 7.02 mol, MgO is 0.27 mol, glucose is 14.9 g, and water is 3300 g;

[0078] In step S2, Li2CO3 is 0.5 mol, FePO4 is 0.63 mol, MnCO3 is 0.35 mol, NH4H2PO4 is 0.37 mol, MgO is 0.02 mol, glucose is 4.7 g, and water is 400 g.

[0079] Example 4

[0080] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0081] In step S1, Li2CO3 is 3.5 mol, FePO4 is 1.54 mol, MnCO3 is 5.25 mol, NH4H2PO4 is 5.46 mol, MgO is 0.21 mol, glucose is 11.6 g, and water is 2600 g;

[0082] In step S2, Li2CO3 is 1.5 mol, FePO4 is 1.44 mol, MnCO3 is 1.5 mol, NH4H2PO4 is 1.56 mol, MgO is 0.06 mol, glucose is 10.8 g, and water is 1100 g.

[0083] Example 5

[0084] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0085] In step S1, Li2CO3 is 4.5 mol, FePO4 is 1.98 mol, MnCO3 is 6.75 mol, NH4H2PO4 is 7.02 mol, MgO is 0.27 mol, glucose is 14.9 g, and water is 3300 g;

[0086] In step S2, Li2CO3 is 0.5 mol, FePO4 is 0.48 mol, MnCO3 is 0.5 mol, NH4H2PO4 is 0.52 mol, MgO is 0.02 mol, glucose is 3.6 g, and water is 400 g.

[0087] Example 6

[0088] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0089] In step S1, Li2CO3 is 3.5 mol, FePO4 is 0.49 mol, MnCO3 is 6.3 mol, NH4H2PO4 is 6.51 mol, MgO is 0.21 mol, glucose is 3.68 g, and water is 2600 g;

[0090] In step S2, Li2CO3 is 1.5 mol, FePO4 is 1.89 mol, MnCO3 is 1.05 mol, NH4H2PO4 is 1.11 mol, MgO is 0.06 mol, glucose is 14.2 g, and water is 1100 g.

[0091] Example 7

[0092] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0093] In step S1, Li2CO3 is 4.5 mol, FePO4 is 0.63 mol, MnCO3 is 8.1 mol, NH4H2PO4 is 8.37 mol, MgO is 0.27 mol, glucose is 4.7 g, and water is 3300 g;

[0094] In step S2, Li2CO3 is 0.5 mol, FePO4 is 0.63 mol, MnCO3 is 0.35 mol, NH4H2PO4 is 0.37 mol, MgO is 0.02 mol, glucose is 4.7 g, and water is 400 g.

[0095] Example 8

[0096] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0097] In step S1, Li2CO3 is 3.5 mol, FePO4 is 0.49 mol, MnCO3 is 6.3 mol, NH4H2PO4 is 6.51 mol, MgO is 0.21 mol, glucose is 3.68 g, and water is 2600 g;

[0098] In step S2, Li2CO3 is 1.5 mol, FePO4 is 1.44 mol, MnCO3 is 1.5 mol, NH4H2PO4 is 1.56 mol, MgO is 0.06 mol, glucose is 10.8 g, and water is 1100 g.

[0099] Example 9

[0100] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that:

[0101] In step S1, Li2CO3 is 4.5 mol, FePO4 is 0.63 mol, MnCO3 is 8.1 mol, NH4H2PO4 is 8.37 mol, MgO is 0.27 mol, glucose is 4.7 g, and water is 3300 g;

[0102] In step S2, Li2CO3 is 0.5 mol, FePO4 is 0.48 mol, MnCO3 is 0.5 mol, NH4H2PO4 is 0.52 mol, MgO is 0.02 mol, glucose is 3.6 g, and water is 400 g.

[0103] Example 10

[0104] This embodiment provides a lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the LATP in step S3 is 100.3 g, and the mass ratio of the lithium iron manganese phosphate precursor to LATP in S2 is 94:6.

[0105] Embodiment 11

[0106] This embodiment provides a lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the LATP in step S3 is 277.4 g, and the mass ratio of the lithium iron manganese phosphate precursor to LATP in S2 is 85:15.

[0107] Example 12

[0108] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that: the inorganic solid electrolyte in step S3 is LAGP (Li 1.2 Al 0.2 Ge 1.8 (PO4)3).

[0109] Embodiment 13

[0110] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of embodiment 1, except that: the inorganic solid electrolyte in step S3 is LLTO (Li 1.5 La 0.17 Ti 0.5 T 0.5 O3).

[0111] Embodiment 14

[0112] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the glucose in step S3 is 74.4 g.

[0113] Embodiment 15

[0114] This embodiment provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the glucose in step S3 is 98.9 g.

[0115] Comparative Example 1

[0116] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that:

[0117] In step S1, Li2CO3 is 4 mol, FePO4 is 0.16 mol, MnCO3 is 7.6 mol, NH4H2PO4 is 7.84 mol, MgO is 0.24 mol, glucose is 1.2 g, and water is 3000 g;

[0118] In step S2, Li2CO3 is 1 mol, FePO4 is 1.16 mol, MnCO3 is 0.8 mol, NH4H2PO4 is 0.84 mol, MgO is 0.04 mol, glucose is 8.7 g, and water is 800 g.

[0119] Comparative Example 2

[0120] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that:

[0121] In step S1, Li2CO3 is 4 mol, FePO4 is 2.16 mol, MnCO3 is 5.6 mol, NH4H2PO4 is 5.84 mol, MgO is 0.24 mol, glucose is 16.2 g, and water is 3000 g;

[0122] In step S2, Li2CO3 is 1 mol, FePO4 is 1.16 mol, MnCO3 is 0.8 mol, NH4H2PO4 is 0.84 mol, MgO is 0.04 mol, glucose is 8.7 g, and water is 800 g.

[0123] Comparative Example 3

[0124] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that:

[0125] In step S1, Li2CO3 is 4.75 mol, FePO4 is 1.615 mol, MnCO3 is 7.6 mol, NH4H2PO4 is 7.885 mol, MgO is 0.285 mol, glucose is 12.1 g, and water is 3500 g;

[0126] In step S2, Li2CO3 is 0.25 mol, FePO4 is 0.29 mol, MnCO3 is 0.2 mol, NH4H2PO4 is 0.21 mol, MgO is 0.01 mol, glucose is 2.2 g, and water is 200 g.

[0127] Comparative Example 4

[0128] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that:

[0129] In step S1, Li2CO3 is 3.25 mol, FePO4 is 1.105 mol, MnCO3 is 5.2 mol, NH4H2PO4 is 5.395 mol, MgO is 0.195 mol, glucose is 8.3 g, and water is 2400 g;

[0130] In step S2, Li2CO3 is 1.75 mol, FePO4 is 2.03 mol, MnCO3 is 1.4 mol, NH4H2PO4 is 1.47 mol, MgO is 0.07 mol, glucose is 15 g, and water is 1300 g.

[0131] Comparative Example 5

[0132] This comparative example provides a lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the LATP in step S3 is 82.7 g, and the mass ratio of the lithium iron manganese phosphate precursor to LATP in S2 is 95:5.

[0133] Comparative Example 6

[0134] This comparative example provides a lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the LATP in step S3 is 299.4 g, and the mass ratio of the lithium iron manganese phosphate precursor to LATP in S2 is 84:16.

[0135] Comparative Example 7

[0136] This comparative example provides a lithium iron manganese phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the LATP in step S3 is 0g, and the mass ratio of the lithium iron manganese phosphate precursor to LATP in S2 is 100:0.

[0137] Comparative Example 8

[0138] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the amount of glucose in step S3 is 64.3 g.

[0139] Comparative Example 9

[0140] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the amount of glucose in step S3 is 108.8 g.

[0141] Comparative Example 10

[0142] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the time for the first sintering in step S1 is 12 hours.

[0143] Comparative Example 11

[0144] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the time for the second sintering in step S2 is 16 hours.

[0145] Comparative Example 12

[0146] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the time for the third sintering in step S3 is 8 hours.

[0147] Comparative Example 13

[0148] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the temperature of the first sintering in step S1 is 750°C.

[0149] Comparative Example 14

[0150] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the temperature of the second sintering in step S2 is 850°C.

[0151] Comparative Example 15

[0152] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the temperature of the third sintering in step S3 is 650°C.

[0153] Comparative Example 16

[0154] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: the particle size D of the lithium manganese iron phosphate precursor in step S2 is 50 =1.2μm.

[0155] Comparative Example 17

[0156] This comparative example provides a lithium manganese iron phosphate positive electrode material, and its preparation method is basically the same as that of Example 1, except that: in step S3, the particle size D of the lithium manganese iron phosphate positive electrode material is 50 =2.0μm.

[0157] Table 1 Lithium manganese iron phosphate positive electrode materials in various embodiments and comparative examples

[0158]

[0159]

[0160]

[0161] The manganese-iron ratio I in Table 1 refers to the molar ratio of manganese to iron in the core of the lithium iron manganese phosphate positive electrode material, and the mass proportion I refers to the mass proportion of the core in the lithium iron manganese phosphate positive electrode material relative to the total mass of the core and the first coating layer; the manganese-iron ratio II refers to the molar ratio of manganese to iron in the first coating layer of the lithium iron manganese phosphate positive electrode material, and the mass proportion II refers to the mass proportion of the first coating layer in the lithium iron manganese phosphate positive electrode material relative to the total mass of the core and the first coating layer; the carbon content refers to the mass proportion of carbon material in the lithium iron manganese phosphate positive electrode material.

[0162] Performance Testing

[0163] 1. Lithium manganese iron phosphate positive electrode material

[0164] 1) The mass content of manganese in lithium manganese iron phosphate positive electrode material shall be determined in accordance with the provisions of Appendix A of YS / T 677-2008;

[0165] 2) The mass content of iron in lithium manganese iron phosphate positive electrode material shall be determined in accordance with the provisions of Appendix B of GB / T 30835-2014;

[0166] The molar ratio of manganese to iron in the lithium manganese iron phosphate positive electrode material is calculated based on the mass content of manganese and the mass content of iron in the lithium manganese iron phosphate positive electrode material.

[0167] 2. Lithium-ion battery

[0168] a. The lithium manganese iron phosphate positive electrode material in Example 1 is used as the positive electrode active material to make a positive electrode sheet, and is assembled into a button battery with a negative electrode sheet, a separator and an electrolyte. Then, the battery is charged and discharged at a current of 0.1C / 0.1C in an environment of 25±5°C and a voltage range of 2.5 to 4.5V to obtain a gram capacity as follows: Figure 2 As shown, according to Figure 2 It can be seen that the gram capacity of the lithium iron manganese phosphate positive electrode material reaches 156 mAh / g; the gram capacity of the lithium iron manganese phosphate positive electrode material in Examples 2 to 15 all reaches this level, indicating that the lithium iron manganese phosphate positive electrode material of the present invention has a higher gram capacity.

[0169] Preparation of positive electrode sheet: Add the binder PVDF to NMP and stir to obtain a glue solution (solid content of 7%), then mix the positive electrode active material, binder PVDF (glue solution), conductive agent SP and multi-walled CNT in a mass ratio of 94:3:2.5:0.5, add NMP, and stir under the action of a vacuum mixer to obtain a uniform positive electrode slurry (solid content of 45%); use an extrusion coater to evenly coat the positive electrode slurry on the positive electrode collector, dry it in an oven, and then cold press it, and cut it according to the required specifications to obtain the positive electrode sheet.

[0170] Preparation of negative electrode sheets: negative electrode active material graphite, conductive agent SP, thickener CMC, and binder SBR are mixed in a mass ratio of 96:1.5:1.1:1.4, and then solvent deionized water is added to the above mixture, and stirred under the action of a vacuum mixer to obtain a uniform negative electrode slurry (solid content is 49%); the negative electrode slurry is evenly coated on the negative electrode collector using an extrusion coater, dried in an oven, and then cold pressed, and cut according to the required specifications to obtain negative electrode sheets.

[0171] Electrolyte: 1M lithium hexafluorophosphate solution, solvent is ethylene carbonate.

[0172] b. The lithium manganese iron phosphate positive electrode material in each embodiment and comparative example is used as a positive electrode active material to prepare a positive electrode sheet, and is assembled with a negative electrode sheet, a separator and an electrolyte into a lithium ion battery, specifically comprising the following steps:

[0173] Preparation of positive electrode sheet: Add the binder PVDF to NMP and stir to obtain a glue solution (solid content of 7%), then mix the positive electrode active material, binder PVDF (glue solution), conductive agent SP and multi-walled CNT in a mass ratio of 94:3:2.5:0.5, add NMP, and stir under the action of a vacuum mixer to obtain a uniform positive electrode slurry (solid content of 45%); use an extrusion coater to evenly coat the positive electrode slurry on the positive electrode collector, dry it in an oven, and then cold press it, and cut it according to the required specifications to obtain the positive electrode sheet.

[0174] Preparation of negative electrode sheets: negative electrode active material graphite, conductive agent SP, thickener CMC, and binder SBR are mixed in a mass ratio of 96:1.5:1.1:1.4, and then solvent deionized water is added to the above mixture, and stirred under the action of a vacuum mixer to obtain a uniform negative electrode slurry (solid content is 49%); the negative electrode slurry is evenly coated on the negative electrode collector using an extrusion coater, dried in an oven, and then cold pressed, and cut according to the required specifications to obtain negative electrode sheets.

[0175] Cell assembly: stack the negative electrode sheet, separator and positive electrode sheet in a "Z" shape in sequence to obtain a bare cell core package; place the core package into a punched aluminum-plastic film shell for side packaging to obtain a lithium-ion battery without air bag sealing.

[0176] Liquid injection, formation, gas extraction, and volume determination: the lithium-ion battery without the air bag sealed is placed in an oven for baking, and after baking, an electrolyte (1M lithium hexafluorophosphate solution, the solvent is ethylene carbonate) is injected into the inner cavity of the battery; after vacuum packaging, standing, formation, gas extraction, secondary sealing, and volume determination, a lithium-ion battery is obtained.

[0177] The above lithium-ion battery was tested as follows, and the test results are shown in Table 2.

[0178] 1) Cycle capacity retention rate: Under 25±5℃ environment, the voltage test range is 2.5V-4.3V, and the charge and discharge cycle is performed at a current of 1C / 1C for 2000 cycles. The discharge capacity of the first cycle is C0, and the discharge capacity of the 2000th cycle is C1. The capacity retention rate = C1 / C0×100%.

[0179] 2) Mass energy density: At 25±5℃, fully charge the battery at 0.33C (charge to 4.3V at constant current and constant voltage), then discharge to 2.5V at 0.33C to obtain discharge energy e. After the lithium-ion battery is evacuated and sealed twice, the cell weight m is obtained, and the mass energy density = e / m.

[0180] Table 2 Performance of lithium iron manganese phosphate positive electrode materials and corresponding batteries in various embodiments and comparative examples

[0181]

[0182]

[0183] According to the data in Table 2, the capacity retention rate of the battery assembled with the lithium iron manganese phosphate positive electrode material in Examples 1 to 15 after 2000 cycles is ≥82%, reaching 82.13% to 93.47%, and the mass energy density reaches 198.4 to 219.8Wh / kg, indicating that the lithium iron manganese phosphate positive electrode material of the present invention not only has excellent cycle performance, but also has a higher energy density.

[0184] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A lithium manganese iron phosphate positive electrode material, characterized in that: It comprises an inner core, a first coating layer arranged on the surface of the inner core, and a second coating layer arranged on the surface of the first coating layer; The core is lithium iron manganese phosphate I, the first coating layer includes lithium iron manganese phosphate II, and the second coating layer includes carbon material and inorganic solid electrolyte; The molar ratio of manganese element to iron element in the lithium manganese iron phosphate I is (0.75-0.9):(0.07-0.24); The molar ratio of manganese element to iron element in the lithium manganese iron phosphate II is (0.35-0.5):(0.47-0.64); Taking the total mass of the core and the first coating layer as 100%, the mass of the core accounts for 70% to 90%; The mass ratio of the total mass of the core and the first coating layer to the mass of the inorganic solid electrolyte is (85-94):(6-15); the mass content of the carbon material in the lithium manganese iron phosphate positive electrode material is 1.5%-2%.

2. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that Satisfy at least one of the following: a. The molar ratio of manganese element to iron element in the lithium manganese iron phosphate positive electrode material is (0.63-0.85):(0.1-0.33); b. The particle size D of the core 50 0.6~1.2μm; c. The inorganic solid electrolyte includes at least one of LATP, LAGP, LLTO, and LLZO.

3. The lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that The lithium iron manganese phosphate I and / or lithium iron manganese phosphate II include doping elements.

4. The lithium iron manganese phosphate positive electrode material according to claim 3, characterized in that: Taking the total molar amount of manganese element, iron element and doping element as 100%, at least one of the following is satisfied: a. The molar content of the doping element in the lithium manganese iron phosphate I is 1% to 3%; b. The molar content of the doping element in the lithium manganese iron phosphate II is 1% to 3%.

5. The method for preparing the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing a lithium source, an iron source, a manganese source, a phosphorus source, a doped metal source, a carbon source and a solvent, sand-milling to obtain a mixed slurry I, spray-drying the mixed slurry, sintering the mixed slurry for the first time in an inert gas atmosphere, and crushing the mixed slurry to obtain lithium iron manganese phosphate seed crystals; S2, mixing the lithium iron manganese phosphate seed crystals in S1 with a lithium source, an iron source, a manganese source, a phosphorus source, a doped metal source, a carbon source and a solvent, sand-milling to obtain a mixed slurry II, spray-drying the mixed slurry, sintering the mixed slurry for a second time in an inert gas atmosphere, and crushing the mixed slurry to obtain a lithium iron manganese phosphate precursor material; S3, mixing the lithium iron manganese phosphate precursor material in S2 with an inorganic solid electrolyte, a carbon source and a solvent, sand-milling to obtain a mixed slurry III, spray-drying the mixed slurry, sintering the mixed slurry for the third time in an inert gas atmosphere, and crushing the mixed slurry to obtain a lithium iron manganese phosphate positive electrode material; The temperature of the first sintering is ≤650°C and the time is ≤8h; the temperature of the second sintering is ≤750°C and the time is ≤15h; the temperature of the third sintering is ≤600°C and the time is ≤8h.

6. The preparation method according to claim 5, characterized in that: Satisfy at least one of the following: a. The first sintering temperature is 350-650°C and the time is 3-8h; b. The temperature of the second sintering is 550-750°C and the time is 4-15h; c. The temperature of the third sintering is 500-600°C and the time is 2-6 hours.

7. The preparation method according to claim 5, characterized in that: Satisfy at least one of the following: a. The particle size D after sand grinding described in S1 50 The particle size after crushing is 150~300nm. 50 0.6~1.2μm; b. The particle size D after sand grinding described in S2 50 The particle size after crushing is 200~380nm. 50 1.5~2.1μm; c. The particle size D after sand grinding described in S3 50 The particle size after crushing is 50~120nm. 50 2.3~3.0μm.

8. The preparation method according to claim 5, characterized in that: Satisfy at least one of the following: a. The molar ratio of Li in the lithium source, Fe in the iron source, Mn in the manganese source, P in the phosphorus source and the doping element in the doping metal source in S1 is (1-1.06):(0.07-0.24):(0.75-0.9):(1-1.05):(0.01-0.03); b. The molar ratio of Li in the lithium source, Fe in the iron source, Mn in the manganese source, P in the phosphorus source and the doping element in the doping metal source in S2 is (1-1.06):(0.47-0.64):(0.35-0.5):(1-1.05):(0.01-0.03); c. The doping metal sources described in S1 and S2 both include a magnesium source, which is at least one of magnesium oxide, magnesium hydrogen phosphate, magnesium hydroxide, and magnesium carbonate; d. The carbon sources described in S1, S2 and S3 are independently selected from at least one of glucose, sucrose, polypropylene, acetylene black and polyvinylpyrrolidone-K30; The lithium sources described in e. S1 and S2 are independently selected from at least one of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, lithium nitrate, lithium oxalate, lithium acetate and lithium phosphate; f. The iron sources described in S1 and S2 are independently selected from at least one of ferric oxalate, ferric phosphate, ferric oxide, ferric hydroxide and ferric acetate; The manganese sources described in g, S1 and S2 are independently selected from at least one of manganese carbonate, manganese oxalate, manganese dioxide, manganese trioxide and manganese tetraoxide; The phosphorus sources described in h, S1 and S2 are independently selected from at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid and lithium dihydrogen phosphate.

9. A positive electrode sheet, characterized in that: It comprises a current collector and a coating disposed on at least one side of the current collector, wherein the coating comprises the lithium manganese iron phosphate positive electrode material according to any one of claims 1 to 4.

10. A battery, characterized in that: Including the positive electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • Polyphosphate positive electrode material, preparation method thereof and secondary battery

    CN115036466A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN115775878A

  • Lithium manganese iron phosphate composite material and positive plate and battery comprising same

    CN116364924A

  • Phosphate positive electrode material, preparation method and lithium battery application

    CN116470021A

Cited By

  • Manufacturing process of lithium iron phosphate energy storage battery

    CN121123420A

  • Preparation method of lithium manganese iron phosphate positive electrode material

    CN121134725A

  • Lithium manganese iron phosphate material as well as preparation method and application thereof

    CN121260796A